2018
DOI: 10.3382/ps/pey163
|View full text |Cite
|
Sign up to set email alerts
|

Short periods of incubation, egg turning during storage and broiler breeder hens age for early development of embryos, hatching results, chicks quality and juvenile growth

Abstract: An effect of modification of storage conditions of the eggs of broiler breeder flocks at the age of 49-, 52- and 70-, 73-wks of life on an early embryonic development, hatching time and synchronization, hatchability rates, chicks quality and broiler growth was investigated. The eggs were divided into 4 experimental groups: COI = eggs storage 5 d, at turning every 12 h; NSP = eggs storage 12 d, at turning every 12 h; SPIDES = were treated with 4 h pre-incubation at 30°C and 50-55% air humidity, delivered at 5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
3
25
1
1
Order By: Relevance
“…These results agree those of Latour et al [ 77 ] who studied hatchlings from Arbor Acres breeder aged of 36 and 51 weeks. Damaziak et al [ 78 ] noted also, a decrease of the chick quality (−5 points based on Tona score) as well as an increase of the chick weight (+9.2 g) with breeder age (49 to 52 weeks vs. 70 to 73 weeks). In the same line, Rifkhan et al [ 79 ] reported the increase of the hatchling weight by +12.72 g and the hatchling length by +1.1 cm when breeder age increased from 26–35 weeks to 46–55 weeks, which is probably related to egg weight at set.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree those of Latour et al [ 77 ] who studied hatchlings from Arbor Acres breeder aged of 36 and 51 weeks. Damaziak et al [ 78 ] noted also, a decrease of the chick quality (−5 points based on Tona score) as well as an increase of the chick weight (+9.2 g) with breeder age (49 to 52 weeks vs. 70 to 73 weeks). In the same line, Rifkhan et al [ 79 ] reported the increase of the hatchling weight by +12.72 g and the hatchling length by +1.1 cm when breeder age increased from 26–35 weeks to 46–55 weeks, which is probably related to egg weight at set.…”
Section: Discussionmentioning
confidence: 99%
“…One of these aspects is egg turning during storage before incubation, which is a management practice applied in other poultry species to promote embryonic development and performance during subsequent incubation. Egg turning improves the interaction of the chorioallantoic membrane with the inner shell membrane, allowing adequate chorioallantoic membrane development when the typical incubation temperature is reached (Elibol et al, 2002;Damaziak et al, 2018). However, there is no consensus in the poultry literature regarding the mechanisms involved in the effects of egg turning during storage, nor on the optimal turning regime (Elibol et al, 2002;Damaziak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Egg turning improves the interaction of the chorioallantoic membrane with the inner shell membrane, allowing adequate chorioallantoic membrane development when the typical incubation temperature is reached (Elibol et al, 2002;Damaziak et al, 2018). However, there is no consensus in the poultry literature regarding the mechanisms involved in the effects of egg turning during storage, nor on the optimal turning regime (Elibol et al, 2002;Damaziak et al, 2018). The most positive effects of egg turning during storage have been reported in eggs from older hens (Damaziak et al, 2018), or in low-quality eggs (Elibol et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Согласно данным К. Damaziak с соавт. (83), выводимость хранившихся яиц от бройлерных кур 70-и 73-недельного возраста, а также качество получаемых от них цыплят хуже, чем в случае 49-и 52недельных самок. Яйца от молодых матерей выдерживают более длительное хранение при высокой температуре и низкой влажности, чем снесенные несушками в конце продуктивного периода (84).…”
unclassified